Unit Weight of Foam Concrete Containing Blended Cement and Fly Ash - Sunarno, Yohans; Tjaronge, M. W.; Irnawaty, Rita; Muhiddin, Achmad Bakri (Jurnal Teknik Sipil dan Perencanaan, 2022)
Abstract. The rapid development of construction and infrastructure results in increasing demands for natural resources continue. One of the many natural elements required for construction and infrastructure activities was cement, which is the basic ingredient in concrete. This study aims to analyze the unit weight of foam concrete containing blended cement and fly ash. The research approach used in this study was a laboratory experiment. Foam concrete was produced using 4 variations of cement (OPC, PCC-T, PCC-B and OPC+FA), fine aggregate, water and foam. The shape of the test object used was cube with a size of 15 cm × 15 cm × 15 cm. Unit weight test was used to evaluate the foam concrete mixture produced at the age of 3, 7, 28 and 730 days. The results showed that the unit weight of foam concrete in all variations of the specimens: OPC, PCC-T, PCC-B and OPC+FA, met the requirements for the unit weight of lightweight structural concrete based on SNI 03-3449-2002 and ACI 213R3 which was between 800 to 1400 kg/m3.